Alkyl phosphonic acid-based ligands as tools for converting hydrophobic iron nanoparticles into water soluble iron–iron oxide core–shell nanoparticles. (18th September 2017) - Gharbi, Kais; Salles, Florent; Mathieu, Paul; Amiens, Catherine; Collière, Vincent; Coppel, Yannick; Philippot, Karine; Fontaine, Laurent; Montembault, Véronique; Smiri, Leila Samia; Ciuculescu-Pradines, Diana
Abstract : Transfer of Fe nanoparticles into water using phosphonates. Abstract : Phosphonic acid derivatives are suitable compounds for controlling the surface properties of materials and nanomaterials. Here, we present for the first time the use of alkyl phosphonic acid ligands to transfer into water zero-valent iron nanoparticles (FeNP ) synthesized by an organometallic approach. The transfer takes place with the formation of an oxide layer at the surface of the iron nanoparticles, beneficial for the coordination of the alkyl phosphonic acid ligands. The nanoparticles are highly soluble in water and present a core–shell structure, with a monocrystalline body-centered cubic iron core of ca. 10 nm in size surrounded by a spinel oxide shell of ca. 2 nm thickness. These hydrophilic nanoparticles display excellent structural stability, magnetization still reaching 70% of that of bulk iron, and a transversal relaxivity r 2 of 335 mM −1 s −1 which give them high potential for biomedical applications.